A PROPOSED AUTOMATIC LOAD SHEDDING SCHEME FOR AN OFFSHORE PLATFORM - ALIAS, ANIS (Universiti Teknologi Petronas, 2006)
The mainobjective of this project is to design an automatic load shedding scheme for an offshore platform (Bekok-C) to halt power failure and total system collapse. The scope of study consists of system analysis that proposes the best approach in doing load shedding, system's calculation and development of Graphical User Interface (GUI) of proposed automatic loadshedding scheme using software. There are two main techniques in doing load sheddingwhich are underfrequency and undervoltage load shedding scheme. Undeniably, underfrequency load shedding is more popular rather than undervoltage due to its efficiency. As total loss of generation occurs within a system, the first indicators are drops in voltage and in frequency, butunfortunately, the voltage drops canalso be caused by system faults. It is recognized, that a drop in frequency is a more reliable indication of loss of generation. Asudden lossof generation will result in a reduction in the frequency at a rate of change which depends on the size of the resultant overload and the inertia constant ofthe system. Under this proposed load shedding scheme, as frequency falls below preset level at certain rate, a predetermined amount of load will be removed to restore the system frequency. Important design considerations of this scheme are maximum anticipated overload, number of load shedding steps, size of load shed at each step and frequency relay settings. Then, load restoration can only be executed either manually or automatically after the system has recovered completely and its normal frequency is restored. Loads will be restored in small blocks sequenced by time delay between successive restorations to allow frequency stabilization.